The role of information and experience for households’ inflation expectations - Conrad, Christian; Enders, Zeno; Glas, Alexander (European economic review, 2022)
Based on a new survey of German households, we investigate the role that information channels and lifetime experience play in households’ inflation expectations. We show that the types of information channels that households use to inform themselves about monetary policy are closely related to their socioeconomic characteristics. These information channels, in turn, have a major influence on the level of perceived past and expected future inflation, as well as on the uncertainty thereof. The expected future change in inflation and the unemployment rate, however, is strongly influenced by individual experience of these variables. Similarly, the expected response of inflation to a change in the interest rate is also shaped by experience. We propose the interpretation that households obtain inflation numbers from the media, but their ‘economic model’ is shaped by experience.
Gesehen am 23.05.2022